Analisis perbandingan manajemen laba dengan metode Discretionary Accrual pada bank syariah dan bank konvensional - Galuh Tri Pambekti (Faculty of Economics, Universitas Islam Indonesia, 2017)
AbstractEarnings management is a deliberate act by managers using their power to determine the policy of regulating the level of corporate earnings. The purpose of this study is to prove that there is a difference between the level of earnings management in Islamic banks and conventional banks. The sample of this research are Islamic banks and conventional banks registered in Bank Indonesia for 2011-2015 The sample used is 96 samples. The testing technique in this study used independent mean test (Independent Sample T-Test). The earning management variables in this study were measured by discretionary accrual, measurement using Modified Jones Model (1991) to calculate total accruals. The results showed that the value of Sig. (2-tailed) is 0,000 indicates that there is a difference between Group A and Group B. It means that there is a difference between discretionary accrual ratio of conventional bank and discretionary accrual ratio of Islamic banks, it can be said there are differences in earnings management between Conventional Bank and Islamic Bank.